Clinical outcomes of women with COVID 19 during pregnancy: an update (BIRDEM Medical Journal, 2020)
In December 2019, a cluster of four cases of pneumonia of unknown etiology in Wuhan, China, were reported to the World Health Organization (WHO). Since then, the world has seen unprecedented effects of this virus on our health and life in general and every country of the world has been affected. Pregnant women are considered the most vulnerable population and clinical trials and research are going on to ensure the safety of mother and the fetus during this pandemic. The data regarding management of pregnancy during COVID-19 era is evolving every day. In this review, we evaluate the recent evidence of the effects of SARS-CoV-2 infection throughout pregnancy and provide a balanced and informed evidence-based management of pregnancy during the COVID- 19 era.Birdem Med J 2020; 10, COVID Supplement: 93-102